2019
DOI: 10.30699/fhi.v8i1.188
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Content of Medical Tourism Facilitator Websites in Iran And Other Countries: A Correspondence Analysis

Abstract: Introduction: Medical tourism is the most important aspect of health tourism. The responsibilities of this industry are mostly undertaken by agencies and facilitators acting as intermediaries between patients and service providers. As a key factor, websites provide extensive services to patients for a better presence in medical tourism market. The present study aimed to compare medical tourism websites and facilitators in Iran and other countries using correspondence analysis.Method: Websites were selected bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…American and Asian websites focused on providing information related to ethical principles, modern communication methods, hospital accreditation and comparing service costs in other countries, while Iranian websites focused on providing general information and information related to tourism and the trip. In the end, the authors suggested that due to the difference in performance of Iranian websites, developers should improve the content and structure of websites based on technical, health and tourism standards in order to attract more tourists [23].…”
Section: Baghbanian Et Al Conducted a Cross-sectional Study On Iran's...mentioning
confidence: 99%
“…American and Asian websites focused on providing information related to ethical principles, modern communication methods, hospital accreditation and comparing service costs in other countries, while Iranian websites focused on providing general information and information related to tourism and the trip. In the end, the authors suggested that due to the difference in performance of Iranian websites, developers should improve the content and structure of websites based on technical, health and tourism standards in order to attract more tourists [23].…”
Section: Baghbanian Et Al Conducted a Cross-sectional Study On Iran's...mentioning
confidence: 99%